Efektivitas Penjaringan dan Vaksinasi Hewan Penyebab Rabies di Kabupaten Tanah Datar, Sumatera Barat - Ni Putu Indah Purnami; Upik Kesumawati Hadi (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
West Sumatra is one of the provinces with endemic status for zoonotic and strategic animal diseases, namely Rabies. As a result of the infection the social and economic losses generated are classified as large, the impact of the fatality of this disease is the death of infected animals and humans. Collaborative efforts by the community and central and regional governments in the prevention, control and eradication of this disease are needed. In addition, the role of students through community service and real work is also needed to support efforts to liberate rabies in the province of West Sumatra. Until now, public knowledge of the importance of rabies vaccination for animal welfare and animal and human health in West Sumatra Province is still lacking, so appropriate methods and strategies are needed to reach West Sumatra Province free from rabies. Keywords: endemic, animal, human health, community service, rabies